1989
DOI: 10.1007/bf00687711
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar myelopathy with multinucleated giant cells in the acquired immune deficiency syndrome (AIDS)

Abstract: Vacuolar myelopathy (VM) is a frequent neurological complication of the acquired immune deficiency syndrome (AIDS). A suspected connection between VM and human immunodeficiency virus (HIV) has been based only on HIV isolation from affected spinal cord tissue. We report here an AIDS patient dying after 14 months of progressive dementia, including 3 months of spinal signs and symptoms. At autopsy, the brain revealed moderate diffuse damage of the white matter compatible with HIV-induced progressive diffuse leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Pathologically, the disease is usually more severe in the mid-thoracic region than in the cervical spinal cord [20, 21]. Most published series on VM describe a predominant involvement of the lateral and posterior columns of the spinal cord [20, 22]; however, in a pathologic study on 20 patients with VM, no significant longitudinal gradient was found in score severity in the posterior, lateral, or anterior columns [21]. Vacuoles are the result of edematous swelling within myelin, with splitting of the lamellae.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, the disease is usually more severe in the mid-thoracic region than in the cervical spinal cord [20, 21]. Most published series on VM describe a predominant involvement of the lateral and posterior columns of the spinal cord [20, 22]; however, in a pathologic study on 20 patients with VM, no significant longitudinal gradient was found in score severity in the posterior, lateral, or anterior columns [21]. Vacuoles are the result of edematous swelling within myelin, with splitting of the lamellae.…”
Section: Discussionmentioning
confidence: 99%
“…Both methods showed that the frequency of infected cells in peripheral blood is much higher in individuals with AIDS than in those who are asymptomatic and seropositive, suggesting that HIV-1 infection of such cells contributes to CD4+ cell depletion in patients with AIDS. Studies of HIV-1 infection in vivo have demonstrated virus in organs showing tissue damage, particularly the CNS (2-16) and lung (33,34 Four of the previous studies identifying HIV-1 in spinal cords found the virus associated with the lesions of vacuolar myelopathy (2,(10)(11)(12)(13), but not all did (6,8,14,15); we believe this disparity most likely stems from differences in the specific methods used to detect HIV-1 and the pathology of the samples. For example, our procedure for in situ hybridization included autoradiograpic exposure for a period of 10-24 days in various experiments, while another study employing in situ hybridization (15) exposed spinal cord specimens for 2-3 days.…”
mentioning
confidence: 93%
“…These data support a role for HIV-1 in the pathogenesis of tissue damage and related clinical disease in infected individuals. (4)(5)(6)(11)(12)(13), with evidence for infection of the astrocyte, oligodendrocyte, endothelial cell, and neuron reported as well (5,6,10). We used in situ hybridization to further investigate HIV-1 pathogenesis in the CNS by studying spinal cords from AIDS patients with a broad range ofcord pathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VM is characterized by numerous vacuolar myelin swellings and macrophages in multiple areas of the spinal cord (31,71,(158)(159)(160)(161)(162)(163). VM predominantly involves the dorsolateral spinal tracts (Fig.…”
Section: Vacuolar Myelopathymentioning
confidence: 99%